Differences Between Younger and Older Patients with Childhood Hodgkin Lymphoma. (1st September 2013) - Pourtsidis, Apostolos; Doganis, Dimitrios; Baka, Margarita; Bouhoutsou, Despina; Varvoutsi, Maria; Synodinou, Maria; Strantzia, Katerina; Kosmidis, Helen
<x xml:space="preserve">Abstract</x> From 1979 to 2006, 74 children with Hodgkin's lymphoma were treated at our center. Among them, 15 (14 boys and 1 girl) and 59 (33 boys and 26 girls) patients were younger and older than 8 years, respectively. Six (40%) children among younger patients and 26 (44%) among older patients had advanced stage disease. We detected 3 (20%) relapses among younger patients and 5 (8.5%) among the older patients. All of younger patients are alive whereas three of the older patients have died. Second malignancy developed in one and three children among younger and older patients, respectively. The only difference that was detected concerning the age was a male predominance among the younger patients.